In Vitro Test of The Mucolytic Activity of The Ethanol Extract of Bajakah (Spatholobus littoralis Hassk.) Root: Uji Aktivitas Mukolitik Ekstrak Etanol Akar Bajakah (Spatholobus littoralis Hassk.) Secara in Vitro - Ade Ferdinan; Yusril Izzamaulana; Adhisty Kharisma Justicia (Journal Pharmasci (Journal of Pharmacy and Science), 2023)
Bajakah root (Spatholobus littoralis Hassk.) is a plant that is often used as traditional medicine. Bajakah root (Spatholobus littoralis Hassk.) contains phenolic compounds, flavonoids, tannins and saponins. This study aims to determine whether the ethanol extract of bajakah root has mucolytic activity or not, so that its usefulness can be clearly and scientifically known. The method used in this study was in vitro using duck egg white as artificial phlegm by comparing the mucolytic activity between ethanol extracts of pirated roots (Spatholobus littoralis Hassk.) with a concentration of formula I 5%, formula II 10%, and formula III 15%. The mucolytic activity was tested using a Brookfield LVT 230 viscometer, then the viscosity was measured and statistical tests were performed with p<0.05. The ethanol extract of pirated roots (Spatholobus littoralis Hassk.) at concentrations of 5%, 10%, and 15% had mucolytic activity in vitro with percentages of 40.78%, 51.35%, and 47.43%, respectively. as a comparison of mucolytic activity of 0.2% acetylcysteine ​​positive control, which was 58.61%. This indicates that the ethanol extract of the root of the bajakah (Spatholobus littoralis Hassk.) has mucolytic activity against duck egg white in vitro.